Hippocampal Lipocalin 2 Is Associated With Neuroinflammation and Iron-Related Oxidative Stress in ob/ob Mice. Issue 5 (24th February 2020) - Jin, Zhen; Kim, Kyung Eun; Shin, Hyun Joo; Jeong, Eun Ae; Park, Kyung-Ah; Lee, Jong Youl; An, Hyeong Seok; Choi, Eun Bee; Jeong, Jae Hun; Kwak, Woori; Roh, Gu Seob
Abstract: Obesity causes brain injuries with inflammatory and structural changes, leading to neurodegeneration. Although increased circulating lipocalin 2 (LCN2) level has been implicated in neurodegenerative diseases, the precise mechanism of neurodegeneration in obesity is not clear. Here, we investigated whether LCN2-mediated signaling promotes neurodegeneration in the hippocampus of leptin-deficient ob/ob mice, which are characterized by obesity, insulin resistance, systemic inflammation, and neuroinflammation. In particular, there was significant upregulation of both LCN2 and matrix metalloproteinase 9 levels from serum and hippocampus in ob/ob mice. Using RNA-seq analysis, we found that neurodegeneration- sortilin-related receptor 1 ( Sorl1 ) and brain-derived neurotrophic factor ( Bdnf ) genes were significantly reduced in the hippocampus of ob/ob mice. We additionally found that the endosome-related WD repeat and FYVE-domain-containing 1 ( Wdfy1) gene were upregulated in ob/ob mice. In particular, iron overload-related mitochondrial ferritin and nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) proteins were increased in the hippocampus of ob/ob. Thus, these findings indicate that iron-binding protein LCN2-mediated oxidative stress promotes neurodegeneration in ob/ob mice.